The Controlled Tongue Prevents Verbal Misdeeds, Slander, Hatred, Bullying, Incivility, Extremism and Radicalism: Islamic Perspective on Ethical Communication - Afifi, Abdullah A (Perwakilan: Journal of Good Governance, Diplomacy, Customary Institutionalization and Social Networks, 2024)
This paper discusses the critical issue of ethical communication, specifically controlling the tongue, a concept deeply embedded in Islamic teachings that holds profound relevance in today’s global context. As societies grapple with the pervasive problems of slander (fitna), discord, hatred, and bullying, the simple yet powerful ethical principle of tongue control emerges as a crucial tool for fostering harmony. In modern times, the spread of fake news and hoaxes has been widely discussed as an external threat to social cohesion, yet the internal discipline of speech—whether metaphorical or literal—has received far less attention. This paper seeks to address this gap by exploring how the Islamic insight to control one’s tongue can effectively prevent the spread of fitna, the escalation of hatred, the prevalence of bullying, and the rise of incivility, extremism, and radicalism. Through narrative construction, the paper examines the deep-seated negative impacts of these harmful practices and underscores the significance of verbal discipline in mitigating them. By highlighting the intrinsic value of controlling the tongue, the paper aims to present a holistic approach to curbing not only external threats like misinformation but also the internal moral lapses that contribute to societal discord, thereby promoting a more peaceful and just world in alignment with Islamic ethical principles.